MMPs-2 and -14 Are Elevated in Eosinophilic Esophagitis and Reduced Following Topical Corticosteroid Therapy. Issue 2 (August 2015) - Beppu, Lisa; Yang, Tom; Luk, Michelle; Newbury, Robert O.; Palmquist, Jacob; Dohil, Ranjan; Kurten, Richard C.; Broide, David H.; Aceves, Seema S.
ABSTRACT: Objectives: Eosinophilic esophagitis (EoE) is a chronic, antigen-mediated disease in children and adults associated with substantial esophageal remodeling and fibrosis. The expression of the remodeling-associated matrix metalloproteinases (MMPs) has not been previously detailed in EoE. Methods: MMP-2 and -14 expression and cellular localization were assessed using real-time quantitative polymerase chain reaction and immunohistochemistry/immunofluorescence in EoE fibroblasts, active and inactive pediatric EoE biopsies, and nondiseased control biopsies. The effect of transforming growth factor (TGF)-β1 treatment on MMP-2 expression in cultured esophageal epithelial (HET1A) cells was analyzed. Results: MMP-2 and -14 mRNA were expressed in EoE fibroblasts and biopsies. Proliferating epithelial cells produced MMP-14 more abundantly in EoE than in controls ( P < 0.001) and the degree of epithelial MMP-14 expression correlated positively with basal zone hyperplasia ( r = 0.65, P = 0.002). EoE lamina propria had higher numbers of MMP-2- and -14-positive cells (906 ± 167 and 701 ± 93 cells/mm 2 ) as compared with controls (258 ± 93 cells/mm 2, P < 0.01 and 232 ± 54 cells/mm 2, P < 0.01), and MMP-14 expression correlated with the severity of fibrosis. Following therapy with topical corticosteroids, MMP-14 and -2 were significantly diminished ( P < 0.01). TGF-β1 increased the expression and secretion of MMP-2 from esophageal epithelial HET1A cells. Conclusions: MMP-2 and -14 are elevated in pediatric patients with EoE and significantly decrease following topical corticosteroid therapy. TGF-β1 increases MMP-2 in esophageal epithelial cells. This alludes to previously unappreciated role for MMPs in EoE-associated esophageal remodeling and a potential positive feedback loop via TGF-β1. Abstract : Supplemental Digital Content is available in the text